Metode Kritik Sanad (Naqd Al-Sanad) - bakar, Abu; Abubakar, Syaikhah Fakrunnisa (STAI YAPIS Takalar, 2025)
Sanad is one of the most important elements of hadith, as it is well known that a hadith consists of three main components: sanad, matan, and rawi. As the second highest source of Islamic law after the Qur’an, hadith requires a high level of credibility in order to serve as a legal foundation and guidance for Muslims. Therefore, the existence of the sanad is crucial because it functions as the chain of transmission that connects a hadith to the Prophet Muhammad (peace be upon him). This element of sanad has often been the subject of criticism and in-depth study by scholars, since the quality of the sanad largely determines whether a hadith is accepted or rejected. In the early period of Islam, the transmission of hadith was generally based on mutual trust between students and their teachers. However, as Islam spread and various interests emerged, scholars found it necessary to establish specific methods and principles for critically examining hadith. The criticism of the sanad is guided by several key criteria: continuity of the chain (ittishal al-sanad), narrators must be classified as tsiqah, encompassing the qualities of ‘adl (integrity) and dhabit (accuracy), the absence of irregularities (shadh), and the absence of hidden defects (‘illah). If all narrators in a hadith fulfill these criteria, the sanad is considered sahih. Subsequently, the hadith must still undergo matan criticism to determine its final quality and its eligibility to serve as a hujjah in Islam.